Bacterial AvrRpt2-Like Cysteine Proteases Block Activation of the Arabidopsis Mitogen-Activated Protein Kinases, MPK4 and MPK11 . Issue 3 (20th May 2016) - Eschen-Lippold, Lennart; Jiang, Xiyuan; Elmore, James Mitch; Mackey, David; Shan, Libo; Coaker, Gitta; Scheel, Dierk; Lee, Justin
Abstract : Bacterial AvrRpt2-like cysteine proteases specifically suppress flagellin-induced phosphorylation of specific Arabidopsis mitogen-activated protein kinases. Abstract: To establish infection, pathogens deliver effectors into host cells to target immune signaling components, including elements of mitogen-activated protein kinase (MPK) cascades. The virulence function of AvrRpt2, one of the first identified Pseudomonas syringae effectors, involves cleavage of the plant defense regulator, RPM1-INTERACTING PROTEIN4 (RIN4), and interference with plant auxin signaling. We show now that AvrRpt2 specifically suppresses the flagellin-induced phosphorylation of Arabidopsis ( Arabidopsis thaliana ) MPK4 and MPK11 but not MPK3 or MPK6. This inhibition requires the proteolytic activity of AvrRpt2, is associated with reduced expression of some plant defense genes, and correlates with enhanced pathogen infection in AvrRpt2-expressing transgenic plants. Diverse AvrRpt2-like homologs can be found in some phytopathogens, plant-associated and soil bacteria. Employing these putative bacterial AvrRpt2 homologs and inactive AvrRpt2 variants, we can uncouple the inhibition of MPK4/MPK11 activation from the cleavage of RIN4 and related members from the so-called nitrate-induced family as well as from auxin signaling. Thus, this selective suppression of specific mitogen-activated protein kinases is independent of the previously known AvrRpt2 targets and potentially represents a novel virulence function of AvrRpt2.